La colonisation francaise au Canada : Manitoba--Territoires du Nord-ouest--Colombie Anglaise ... - Foursin, Pierre (Ottawa : S. E. Dawson, 2015)
"The author, a Frenchman, joined the delegation of farmers which toured Canada in 1890 by the invitation of Sir Charles Tupper." -- Lowther, B. J., & Laing, M. (1968). A bibliography of British Columbia: Laying the foundations, 1849-1899. Victoria, BC: University of Victoria, p. 104. ...